Longer Daily Duration of Supervised Rehabilitation after Laparoscopic Surgery for Colorectal Cancer Improves Activities of Daily Living - Takuaki Tani; Shinobu Imai; Kiyohide Fushimi (Medical Journals Sweden, 2022)
Objective: To evaluate the effect of a supervised rehabilitation programme with longer hours per day on activities of daily living after laparoscopic surgery for colorectal cancer. Design: This study represents retrospective observational use of nationwide administrative data. Patients: Eligible patients (n = 8,633) were first diagnosed with colorectal cancer between 1 April 2017 and 31 March 2018, underwent laparoscopicassisted colorectal resection, and began rehabilitation within 3 days of surgery. Methods: Patients underwent a long (40 min or more) or short (less than 40 min) supervised rehabilitation programme, defined as rehabilitation under physiotherapist and occupational therapist supervision. The main outcome measure was improvement in activities of daily living from postoperative day 0 to day 14 using Nursing Need Degree. Results: Patients who underwent longer daily supervised rehabilitation (n = 7,173) showed greater improvements in activities of daily living at 14 days after laparoscopic surgery than patients who underwent shorter daily supervised rehabilitation (n = 1,460) (odds ratio (95% confidence interval; 95% confidence interval): 1.42 (1.22-1.64), p < 0.001). The rate of postoperative complications did not differ between groups. Conclusion: Longer daily supervised rehabilitation for colorectal cancer improves activities of daily living after laparoscopic surgery. LAY ABSTRACT Post-operative rehabilitation is performed for muscle weakness, decreased range of motion of joints, and pain caused by surgery, in order to promote recovery and help patients with activities of daily living after surgery. Supervised rehabilitation provides the patient with a programme based on their postoperative condition and background. Laparoscopic surgery for colorectal cancer, the focus of this study, is minimally invasive and results in less postoperative decline than other surgeries. The aim of this study was to evaluate the effect of a supervised rehabilitation programme with longer daily duration on the ability of patients (n = 8,633) to perform activities of daily living after laparoscopic surgery for colorectal cancer. The results show that engaging in daily supervised rehabilitation for longer duration (40 min or more) after laparoscopic surgery for colorectal cancer improves activities of daily living.